A Multivariate Markov Regime‐Switching High‐Frequency‐Based Volatility Model for Optimal Futures Hedging. Issue 11 (2nd March 2017) - Lai, Yu‐Sheng; Sheu, Her‐Jiun; Lee, Hsiang‐Tai
Abstract : This study proposes a multivariate Markov regime‐switching high‐frequency‐based volatility (MRS‐HEAVY) model for modeling the covariance structure of spot and futures returns, and estimating the associated hedge ratios. S&P 500 equity index data are used in estimations, and the results reveal that the MRS‐HEAVY model has a shorter response time than that of the Markov regime‐switching GARCH model; this difference is more pronounced in the high‐volatility regime than in the low‐volatility regime. Out‐of‐sample hedging exercises illustrate that the MRS‐HEAVY exhibits superior hedging performance in terms of both variance reductions and utility gains; it is robust even when transaction costs are considered. © 2017 Wiley Periodicals, Inc. Jrl Fut Mark 37:1124–1140, 2017